FAKTOR-FAKTOR PENGHAMBAT PEMBELAJARAN ONLINE PADA MASA PANDEMI COVID-19 DI SMA NEGERI 1 KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Vira Mayang Sari; Zaili Rusli; Febri Yuliani (Journal Publicuho, 2021)
The purpose of the research is to explain inhibiting factors for online learning during the Covid-19 pandemic in the Senior High School 1 Kuantan Mudik, Kuantan Singingi Regency. This research used qualitative research methods. The selection of the research informans using purposive sampling technique. Primary data collection from interviews, and secondary data from documentation and literature review. Data analysis using an interactive model. From the results of the research conducted, it was found that several factor inhibiting online learning during the Covid-19 pandemic at the Senior High School 1 Kuantan Mudik, Kuantan Singingi Regency, namely the problem of learning facilities, internet connection, and low students motivation. For this reason, the government needs to maximize online learning facilities that can be applied in every school, and educators and parents of students from Senior High School 1 Kuantan Mudik are expected to improve their supervision and ability to use technology and create an active atmosphere and enthusiasm for learning.